HOLISTIC STUDENT MANAGEMENT STRATEGY FOR STRENGTHENING CHARACTER: CASE STUDY AT SMP MUHAMMADIYAH 7 COLOMADU - Intan Dian Saputri; Mahasri Shobahiya; Ari Anshori (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The weak character of students in terms of discipline, responsibility, and empathy is one of the main challenges in education today. The government responded to this problem through SEB No. 1 of 2025 which emphasizes the importance of strengthening character in the school environment through planned and sustainable activities. This study aims to describe the practice of holistic student management at SMP Muhammadiyah 7 Colomadu, analyze its role in shaping student character, and identify obstacles and opportunities for its implementation. The study used a qualitative approach with a phenomenological method, with data collection techniques in the form of observation, in-depth interviews, and documentation. The main informant was the Vice Principal for Student Affairs. The results of the study showed that the school implemented comprehensive student management, from planning, organizing, to program evaluation. Activities such as Dhuha prayer, coding, debate, and cadre formation through IPM contributed to shaping the values ​​of religiosity, leadership, discipline, and social responsibility of students. The main obstacles came from the negative influence of the external environment and lack of family involvement, while opportunities were supported by a strong school culture and the active role of students and parents. This study concludes that holistic student management plays a significant role in shaping student character and can be used as a model for implementing sustainable character education